(Ré)apprendre à être un animal. Carrières interspécifiques en Bolivie - Gaspard, Renault (Anthropologica, 2020)
Based on an ethnography conducted in a centre for the reintroduction of woodland animals in Bolivia, this article proposes to examine the anthropozoological dynamics between volunteers and Capuchin monkeys present in the centre. The analysis of the constraints inherent to the process of animal reintroduction supports a distinction between various forms of rehabilitation. As regards the notion of interspecific trajectories, observations and interviews show the influence that human and non-human trajectories have on each other within the shelter